Subjective evaluation of natural high‐saturated images on a wide gamut display. Issue 6 (13th July 2019) - Kumakura, Erika; Schmid, Katja; Yokosawa, Kazuhiko; Werner, Annette
Abstract: In previous studies of image evaluation using wide color gamut displays, it is unclear to what degree people prefer the chroma‐varying images, especially the images that are more saturated than the most preferred image. Here, we present a study using a wide color gamut display, which measured viewers' most preferred level of image chroma (experiment 1) and their subjective evaluation of images that were less or more saturated than the previously most preferred one (experiment 2). The results showed that (a) the subjects' preferences for the original or for more saturated images depended on the images' original chroma and (b) the subjective evaluation of the images, that is, Valence and Arousal, did not deteriorate when the chroma of images increased more than the most preferred level. Such results indicate that the increase of the image chroma in wider color gamut displays can have a substantial influence on the impression images have on viewers.